G344(P) Copying letters to families: Do we do it and can they read it?. (27th April 2016) - Thomas, N; Yip, G; Tuthill, D
Abstract : Background: Department of Health (DoH), BMA and GMC good practice guidelines all recommend that any letter written about a patient should be copied to them. This should be the default unless there is a clear reason not to do so. The DoH advises that letters should be written in "Plain English" to assist comprehension. "Plain English" corresponds to a reading age of 13–15 years; or the readability (ease of reading) of BBC Online or Readers Digest magazine. 33% of local consultants routinely copied letters in 2008 and 43% in 2011. Aims: Assess whether clinicians in our general paediatrics department copy letters to the families and compare this to previous audit. Assess their readability Methods: All general paediatric clinic letters from a typical week were obtained from the hospital's Intranet and copied into Microsoft Word. We recorded the grade of the letter writer, and whether each letter had been copied to the family. The body of the letter was then scored for ease of reading using Microsoft Word readability software (Flesch reading ease). Results: 110 letters were analysed: 77 by consultants and 33 by juniors. Overall, about two thirds were copied to parents. The mean Flesch reading ease scores were within the recommended range for a general readership, but there was variability, and half of letters from non-Consultant grade doctors were too difficult. The difference between consultants and juniors in copying rates, and in letters being too difficult, was not statistically significant (Chi squared). Consultant's letters were slightly easier to read according to mean scores (p < 0.05, student t-test). Conclusion: Most letters are now copied to families; double the 2008 rate. The majority are sufficiently easy to read, but a significant minority are too difficult even before complex medical terminology is taken into account. Readability scoring tools may be a useful adjunct for gauging whether letters are readable, along with obtaining direct feedback from families.